Pengaruh Faktor Predisposisi, Faktor Pendorong Dan Faktor Pendukung Terhadap Pencatatan Rekam Medis di RSUD Dr. RM Djoelham Binjai - Giyatno; Megawati (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2021)
Law of the Republic of Indonesia number: 29 of 2004 concerning Medical Practice, which includes the obligation of doctors and dentists to make medical records. The results of the evaluation of the completeness of medical records in RSUD Dr. RM Djoelham Binjai still found incomplete medical record files. This study aims to determine the effect of predisposing factors (knowledge, attitudes), driving factors (support from other officers) and supporting factors (facilities and facilities, regulations) on the behavior of doctors in recording medical records. The research design used in this study was a descriptive analytic survey with a cross sectional design, a sample of 29 doctors and quantitative data analysis with univariate, bivariate and multivariate analysis. Based on the results of the chi square test, it was obtained that Knowledge variable p = 0.001, Attitude power p = 0.002, other support staff p = 0.000, facilities and facilities p = 0.002 and settings p = 0.007 multivariate test showed that of the 5 variables tested multiple logistic regression showed variable which has a p-value > 0.05. Based on the results of the multiple logistic regression test, the significant value of the model together was obtained at 0.002 < 0.05, which means that the four variables used as models have a significant influence on Medical Record Recording, the factor that has the greatest influence on Medical Record Recording is the Support Personnel variable. Others are indicated by an OR value of 0.062. The conclusion in this study is that there is an influence, Knowledge, Attitude, Support of Other Personnel, Facilities and Facilities, and Regulations on the Completeness of Medical Record Recording. It is hoped that doctors do not delay in recording complete medical records.